A Review of Studies on the Effects of Blood Flow Restriction Training on Endurance Athletes - Xiao, Junjie; Fu, Daoling (International Journal of Education and Humanities, 2025)
In the context of the Healthy China Strategy and the national goal of building a sports power, marathon and half-marathon events are developing rapidly, reflecting a growing public enthusiasm for endurance sports. This momentum has led to a rising demand among mass elite athletes—non-professional but high-performing runners—for efficient and scientifically grounded training models. However, traditional high-intensity training methods often pose risks of overtraining or injury. In this context, Blood Flow Restriction Training (BFRT), known for its “low-load-high-benefit” profile, emerges as a promising alternative. The objective of this study is to systematically explore the conceptual framework and physiological mechanisms of BFRT, assess its current application in endurance sports both domestically and internationally, and evaluate its potential benefits and limitations specifically for mass elite half-marathon athletes. This study adopts a literature review methodology, integrating empirical findings from sports science databases, journal publications, and expert analyses to map the research landscape surrounding BFRT. Findings indicate that BFRT can significantly enhance lower limb muscle strength, capillarization, and endurance performance when used appropriately. However, research involving mass elite half-marathon athletes remains limited, with gaps in long-term intervention studies, individualized training parameters, and understanding of BFRT's integration with traditional endurance programs. The future research prioritizes longitudinal studies to examine BFRT’s sustained effects, optimize cuff pressure, frequency, and duration specific to endurance demands, and investigate its synergistic potential when combined with conventional aerobic training. These efforts are essential to ensure the safe, targeted, and effective implementation of BFRT in endurance sports development